«BLIND PHARISEES» AND «PEOPLE’S SERVANT»: THE IDEOLOGEME OF «ENEMY» IN G. GREBENSHCHIKOV’S AUTO-MYTH-MAKING - A. Yu. Gorbenko (Вестник Кемеровского государственного университета, 2015)
The paper deals with the strategy of G. Grebenshchikov’s auto-myth-making. The beginner Siberian writer constructed a myth about «a writer from the common people», using which he accomplished the task of entering the literary world. The author came to the conclusion that the key feature of making up a literary biography became a negative identification concerning the intelligentsia which occupied the position of a symbolic «enemy» of the writer.